2009
DOI: 10.1007/s00359-009-0471-2
|View full text |Cite
|
Sign up to set email alerts
|

No neural evidence for dynamic auditory tuning of the A1 receptor in the ear of the noctuid moth, Noctua pronuba

Abstract: By examining the mechanical properties of the tympanum of the noctuid moth, Noctua pronuba, Windmill et al. (2006) suggested that this insect increases (up-tunes) the frequencies of its best hearing when exposed to high intensity sounds (HIS) resembling the echolocation calls of attacking bats. We tested whether this biophysical phenomenon was encoded in the neural responses of this moth's most sensitive auditory receptor (A1 cell) before and after exposure to HIS. We measured: (1) the number of A1 action pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, this phenomenon would represent a significant adaptation only if the biophysical responses were reflected by similar shifts in neural responses as encoded by the auditory receptors. Unfortunately, a previous attempt to find a neuronal correlate of the tympanal uptuning of the ear in N. pronuba failed to find any changes in the moth's auditory frequency sensitivity [Asi et al, 2009]. So far, the moth auditory system seems unable to follow frequency shifts and two-tone bats could profit from this.…”
Section: Discussionmentioning
confidence: 97%
“…However, this phenomenon would represent a significant adaptation only if the biophysical responses were reflected by similar shifts in neural responses as encoded by the auditory receptors. Unfortunately, a previous attempt to find a neuronal correlate of the tympanal uptuning of the ear in N. pronuba failed to find any changes in the moth's auditory frequency sensitivity [Asi et al, 2009]. So far, the moth auditory system seems unable to follow frequency shifts and two-tone bats could profit from this.…”
Section: Discussionmentioning
confidence: 97%
“…The observed up-tuning could be an inherent consequence of the biophysics of the auditory receptor organ and is not related to the relevance of sounds, or it could serve a general energy saving function. It has been suggested that the dynamic changes observed in the tympanic resonance could be a result of changes in the vibrational characteristics of the tympanum after the tensioning of thoracic musculature upon hearing loud sounds (Asi et al 2009). In addition, active sensillar processes or flight musculature that might affect tympanal tension or respiratory oscillations that affect the air pressure behind the tympanum could cause an upward shift in the auditory characteristic frequencies of the moth ear.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of a dynamic up-tuning of the tympanum in the moth Noctua pronuba (Windmill et al 2006) when exposed to bat-like acoustic signals indeed suggested that predation pressure could have resulted in an evolutionary response of the prey. Tympanal dynamic tuning, however, was not obvious in the neuronal auditory responses of N. pronuba (Asi et al 2009) and different physiological conditions during experiments (i.e. changes on the tracheal system or muscular control) could be an explanation for the discrepancy between the mechanical and the neuronal responses of this ear.…”
Section: Introductionmentioning
confidence: 87%
“…In characterizing moth audition, however, it is important to keep in mind that not every mechanical event implicates a neuronal correlate. For example, the dynamic tuning in resonant frequency that takes place in the mechanical vibration response of the stigma in N. pronuba when stimulated with high-intensity sounds does not seem to affect the neuronal response of the A1 auditory receptor (Asi et al, 2009). There is no doubt that further research into the tympanum of the moth will continue to demonstrate that it is not a simple system.…”
Section: Using the Distortion-products Mechanical Audiograms To Charamentioning
confidence: 99%